IMPLEMENTASI MODEL PEMBELAJARAN PROJECT BASED LEARINING (PJBL) BERBASIS VIDEO PEMBELAJARAN INTERAKTIF TERHADAP MINAT BELAJAR SISWA - Adawiyah, Robiatul; Surani, Dewi; Hidayat, Amat (Information Technology Education Department, 2024)
The rapid advancement of technology forces every individual to face increasingly complex challenges. This also has an impact on the world of education, where the ability of learners is developed along with the times. This study aims to determine whether there is an influence and difference in student learning interest using a project-based learning model (PJBL) with the help of interactive learning videos in video editing subjects. The research method used is a pseudo-experimental design with a quantitative approach, and data collection is done through a questionnaire given to 66 grade X students at SMK Darus Syifa in Cilegon city. The results showed that the application of the project-based learning model influenced student interest in learning, and there were differences in the increase in the average percentage of questionnaire scores, where the control class had an average score of 53.26% while the experimental class reached 60.69%. This research is expected to be a learning model in basic video editing subjects and provide benefits for teachers, students, and future researchers.